2018
DOI: 10.1113/jp276933
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disordered breathing in children disrupts the maturation of autonomic control of heart rate and its association with cerebral oxygenation

Abstract: Key points Sleep disordered breathing (SDB) affects 4–11% of children and is associated with adverse neurocognitive, behavioural and cardiovascular outcomes, including reduced autonomic control. The relationship between heart rate variability (HRV; a measure of autonomic control) and age found in non‐snoring control children was absent during sleep in children with SDB. Age significantly predicted increasing cerebral oxygenation during wake in non‐snoring control children, whereas during sleep, HRV significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…On the contrary, Finley and Nugent 24 studied 61 healthy participants from 1 month until 24 years of age during wakefulness, quiet sleep, and active sleep and showed that HRV changed with age with a gradual increase in parasympathetic modulation in the first 6 years of life, with a following gradual decrease. Finally, Walter et al 25 recently reported that in individuals without disorders, age is associated with increasing parasympathetic and sympathetic activity (LF power) during both wakefulness and sleep during the developmental period. Thus, similarly to many other sleep features, HRV does show age-related changes during the developmental period that still need to be detailed in more refined studies.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Finley and Nugent 24 studied 61 healthy participants from 1 month until 24 years of age during wakefulness, quiet sleep, and active sleep and showed that HRV changed with age with a gradual increase in parasympathetic modulation in the first 6 years of life, with a following gradual decrease. Finally, Walter et al 25 recently reported that in individuals without disorders, age is associated with increasing parasympathetic and sympathetic activity (LF power) during both wakefulness and sleep during the developmental period. Thus, similarly to many other sleep features, HRV does show age-related changes during the developmental period that still need to be detailed in more refined studies.…”
Section: Discussionmentioning
confidence: 99%
“…Despite most studies concluding that fNIRS recordings tend to be abnormal in children with SDB, fNIRS‐derived cerebral oxygenation parameters have not been able to explain the higher prevalence of problem behaviors in children with SDB despite the promising aspects of this method. A major advance was a study by Walter et al 43 that helped characterize adverse neurobehavioral outcomes of SDB better by examining the link between impaired autonomic control and cerebral hemodynamics. The authors demonstrated that SDB disrupts the normal maturation of the autonomic control of heart rate and the association between heart rate variability and cerebral oxygenation exhibited by nonsnoring controls.…”
Section: Discussionmentioning
confidence: 99%
“…This corroborates with another study in children aged between three and 12, which concluded that sleep-disordered breathing with frequent hypoxia disrupt the maturation of the ANS. 30 On the other hand, Urbanik et al 14 demonstrated that patients with OSAS had reduced HRV in the time-domain and spectral parameters, and that these changes occur not only during sleep, but also during daily activity. Data herein demonstrated the presence of OSAS in 30% of the sample.…”
Section: Discussionmentioning
confidence: 99%